UJI EFEKTIVITAS KONSENTRASI KOMBINASI CAMPURAN EKSTRAK DAUN KEMANGI DENGAN DAUN PANDAN WANGI SEBAGAI PENOLAK LALAT RUMAH - selviana; Deli Atika; Ufi Ruhama; Helfi Nolia; Khairul Bariyah (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Vector borne disease spreads widely and rapidly every year. House flies can act as vectors for various diseases namely typhoid, stomach ache such as dysentery, cholera, diarrhea and skin diseases that can cause death in many countries. Therefore the effective and safe control is needed, one of which is biological control. Among other things, biological control can use plants as a repellent. This thesis have a goals to known the effectivenness test of combination kemangi leaf concenterate (Ocimum basilicum forma citartum) with pandan wangi (Pandanus amaryllfolius Roxb) as a flies repellent. This thesis using true experiment design with 360 flies as a sample that taking from Wonodadi traditional market, with 6 cycle and 15 minute observation. The research doing in Dinas Lingkungan Hidup Kuburaya Regency Laborotary. The researcer using One Way Anova with 95% (?=0,05) signification as a statistic test. The result of this research show that there are some significant different amount of the flies that pearch to the bait before and after the treatment with 5%, 10%, and 15% dose control. The researcher wish this research can be the alternatif to repellent the flies at house.